GRP75 as a functional element of cholix transcytosis. Issue 1 (2nd January 2023) - Liu, Keyi; Hunter, Tom; Taverner, Alistair; Yin, Kevin; MacKay, Julia; Colebrook, Kate; Correia, Morgan; Rapp, Amandine; Mrsny, Randall J.
ABSTRACT: Cholix (Chx) is secreted by non-pandemic strains of Vibrio cholerae in the intestinal lumen. For this exotoxin to induce cell death in non-polarized cells in the intestinal lamina propria, it must traverse the epithelium in the fully intact form. We identified host cell elements in polarized enterocytes associated with Chx endocytosis and apical to basal (A→B) vesicular transcytosis. This pathway overcomes endogenous mechanisms of apical vesicle recycling and lysosomal targeting by interacting with several host cell proteins that include the 75 kDa glucose-regulated protein (GRP75). Apical endocytosis of Chx appears to involve the single membrane spanning protein TMEM132A, and interaction with furin before it engages GRP75 in apical vesicular structures. Sorting within these apical vesicles results in Chx being trafficked to the basal region of cells in association with the Lectin, Mannose Binding 1 protein LMAN1. In this location, Chx interacts with the basement membrane-specific heparan sulfate proteoglycan perlecan in recycling endosomes prior to its release from this basal vesicular compartment to enter the underlying lamina propria. While the furin and LMAN1 elements of this Chx transcytosis pathway undergo cellular redistribution that are reflective of the polarity shifts noted for coatamer complexes COPI and COPII, GRP75 and perlecan fail to show these dramatic rearrangements. Together, these data define essential steps in the A→B transcytosis pathway accessed by Chx to reach the intestinal lamina propria where it can engage and intoxicate certain non-polarized cells. One Sentence Summary: The Vibrio cholerae exotoxin protein cholix interacts with a number of host cell proteins, including GRP75, to facilitate its vesicular transcytosis across polarized intestinal epithelial cells following apical endocytosis.